Enhancing alfalfa and sorghum silage quality using agricultural wastes: fermentation dynamics, microbial communities, and functional insights - Yuanyuan Zhao; Dianpeng Liu; Yulian Chen; Yao Lei; Maoya Li; Jiachuhan Wang; Xiangjiang He; Yu Yang; Xinyi Zhang; Shengnan Liu; Xiaoqing Zhang; Qiming Cheng; et al. (BMC Plant Biology)
Abstract At present, there are many researches on the nutritional quality and fermentation quality of forage silage by adding distillers’ grain and fruit residue, but few researches on the succession and function prediction of microbiotic community. In this study, the potential of Moutai distillers' grain (MDG), Rosa roxburghii pomace (RP) and Lactobacillus acidophilus (LAB) to improve silage quality during anaerobic storage of alfalfa and sorghum was investigated. Harvested alfalfa and sorghum were ensiled without (CK) or with MDG, RP, LAB, LAB + MDG or LAB + RP for 45 days at 21–25 °C. Compared with the uninoculated control, alfalfa silage inoculated with LAB + MDG presented better nutrient retention, where the lactic acid (LA) content was increased by 84.62% and the ammonia nitrogen (AN) content was reduced by 38.52%. Similarly, in sorghum silage, both inoculation with LAB + MDG and inoculation with LAB + RP effectively increased nutrient retention, increased the LA content and reduced the AN content. The proportion of Lactobacillus increased in sorghum and alfalfa silage after 45 days of fermentation. Inoculation of alfalfa and sorghum with RP or LAB + MDG significantly increased the relative abundance of lactic acid bacteria in silage, especially Lactobacillus plantarum, which was the main dominant strain. The addition of MDG to the feeds not only effectively retained the crude protein (CP) content of the feeds for better retention of their nutritional value but also significantly reduced the contents of neutral detergent fiber (NDF) and acid detergent fiber (ADF), which improved the digestibility and utilization of the feeds. In addition, the addition of MDG further promoted the proliferation of Lactobacillus and increased their abundance in the silage, thus contributing to the improvement of fermentation quality and preservation of silage. In summary, MDG, LAB + MDG, and RP + LAB resulted in higher-quality silage, but the addition of MDG was more cost effective and therefore is recommended for application in production.